2021
DOI: 10.3390/ani11082405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Slow-Release Urea Administration on Production Performance, Health Status, Diet Digestibility, and Environmental Sustainability in Lactating Dairy Cows

Abstract: The effects of partially replacing soybean meal (SBM) with a slow-release urea source (SRU) on production performance, feed efficiency, digestibility, and environmental sustainability of dairy cows were evaluated. A total of 140 lactating Holstein Frisian cows were allocated into two study groups: (i) control (diet entirely based on SBM), and (ii) treatment (diet of 0.22% on dry matter basis (d.m.)) of SRU. Milk yield, dry matter intake (DMI), feed conversion rate (FCR), body condition score (BCS), reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…Moreover, several studies reported that the lower dose of SRU actually resulted in better growth performance of yak fed diet supplemented with 1% than with 2% of SRU [8] or the higher fibre digestibility of a high-grain diet with 0.5% and 1% SRU than 1.75% SRU supplementation in Rusitec [9]. For lactating dairy cows, Grossi et al reported that inclusion of 1.33% SRU to partly replacing feed protein in dairy cow diet improved feed intake, milk yield and production efficiency as well as reduced methane production and carbon footprint due to SRU feeding [11]. In a metaanalysis, Salami et al found that supplementation of dairy cow diets with SRU was beneficial to improve feed efficiency and to decrease carbon footprint and manure nitrogen excretion but limited effect on milk production [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies reported that the lower dose of SRU actually resulted in better growth performance of yak fed diet supplemented with 1% than with 2% of SRU [8] or the higher fibre digestibility of a high-grain diet with 0.5% and 1% SRU than 1.75% SRU supplementation in Rusitec [9]. For lactating dairy cows, Grossi et al reported that inclusion of 1.33% SRU to partly replacing feed protein in dairy cow diet improved feed intake, milk yield and production efficiency as well as reduced methane production and carbon footprint due to SRU feeding [11]. In a metaanalysis, Salami et al found that supplementation of dairy cow diets with SRU was beneficial to improve feed efficiency and to decrease carbon footprint and manure nitrogen excretion but limited effect on milk production [12].…”
Section: Introductionmentioning
confidence: 99%
“…Heat stress can reduce rumen microorganisms' degradation and reproduction ability by changing rumen tissue morphology, rumen temperature, pH, and osmotic pressure, which is not conducive to nutrient digestion and absorption, and thus reduce the production performance and feed conversion rate of animals [21]. Animal studies demonstrate that replacing SM with SRU can be a strategy to enhance dairy cows' sustainability due to improved production efficiency [18]. Supplementing ruminant diets with SRU can increase the consistency of the link between rumen energy and protein availability and enhance microbial protein synthesis, thus improving its conversion efficiency into milk [22].…”
Section: Discussionmentioning
confidence: 99%
“…According to the experimental method described by Grossi [18], the correlation coefficient between the predicted value and the measured value reached 0.880. Therefore, the prediction was made according to the following formula: CH 4 (g/d) = 2.54 + 19.14 × DMI where:…”
Section: Environmental Impact: Predicted Enteric Methane Productionmentioning
confidence: 96%
“…Environmental factors present increasingly complex challenges to the dairy sector. Global climate change, soil degradation, and competition for finite land resources have wide-ranging implications for agriculture as a whole [23][24][25]. Assessing and mitigating the specific carbon and water footprints associated with dairy production represents an area of increasing importance [26].…”
Section: Literature Reviewmentioning
confidence: 99%